Adjustment constraints in developing countries: A comparative study - Rasul Shams (Intereconomics, 1989)
The debt crisis of the eighties has compelled many developing countries to catch up on a painful adjustment backlog. In addition to traditional stabilization measures sponsored by the IMF, many countries are now acquainted with the structural adjustment programmes of the World Bank. Some have implemented these programmes successfully, others have terminated them after a short period or only partially completed them. What are the reasons for this?
Keywords: 330; Development Policy